2014
DOI: 10.1186/1687-1847-2014-319
|View full text |Cite
|
Sign up to set email alerts
|

On a fourth order elliptic equation with supercritical exponent

Abstract: This paper is concerned with the semi-linear elliptic problem involving nearly critical exponent (P ε ):where is a smooth bounded domain in R n , n ≥ 5, and ε is a positive real parameter. We show that, for ε small, (P ε ) has no sign-changing solutions with low energy which blow up at exactly three points. Moreover, we prove that (P ε ) has no bubble-tower sign-changing solutions. MSC: 35J20; 35J60

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Concerning the supercritical case, namely q = N+4 N−4 + ε with ε > 0, when K is a constant, Bouh [6] showed that there is no sign-changing solution with low energy which blow up at exactly two points for ε small and proved that problem (1.3) has no bubble-tower sign-changing solutions. Ayed and Mehdi [4] got that the supercritical problem (1.3) has no solutions which concentrate around a point of Ω as ε → 0.…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 99%
“…Concerning the supercritical case, namely q = N+4 N−4 + ε with ε > 0, when K is a constant, Bouh [6] showed that there is no sign-changing solution with low energy which blow up at exactly two points for ε small and proved that problem (1.3) has no bubble-tower sign-changing solutions. Ayed and Mehdi [4] got that the supercritical problem (1.3) has no solutions which concentrate around a point of Ω as ε → 0.…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 99%